Spectral Properties and Beam Quality of Long Cavity High Power Semiconductor Tapered Lasers Emitting at Red Region using Reflecting Bragg Grating - Nguyen, Thanh Phuong (Old Journal, 2019)
The wavelength of 4 mm cavity length high-power Semiconductor Tapered lasers are stabilized by Reflecting Bragg Grating. Optical output power of laser system reaches 1 W at working temperature of 25ºC. The laser operates at a stable single longitudinal mode with emitting wavelength of 670.95 nm. Up to optical output power of 0.5 W, the laser beam quality defined by beam propagation ratio M² at 1/e² intensity profile level remains nearly diffraction-limited value of the perfect Gaussian beam. At higher optical powers, the beam propagation ratio increases remarkably because of the broadening of beam waist diameter.